A decade (2008–2017) of water stable isotope composition of precipitation at Concordia Station, East Antarctica - DREOSSI G; MASIOL M; STENNI B; ZANNONI D; SCARCHILLI C; CIARDINI V; CASADO M; LANDAIS A; WERNER M; CAUQUOIN A; CASASANTA G; DEL GUASTA M; et al. (The Cryosphere, 2024)
A 10-year record of oxygen and hydrogen isotopic composition of precipitation is presented here: from 2008 to 2017, 1483 daily precipitation samples were collected year-round on a raised platform at Concordia Station, East Antarctica. Weather data were retrieved from the Italian Antarctic Meteo-Climatological Observatory automatic weather station (AWS), while ERA5 was used to estimate total precipitation. The δ–temperature relationships were moderately high for daily data (r2=0.63 and 0.64 for δ18O and δ2H, respectively) and stronger using monthly data (r2=0.82 for both δ18O and δ2H), with a slope of about 0.5 ‰ °C−1 for (3.5 ‰ °C−1 for ), which remains consistent also using annual averages. The isotopic composition of precipitation is the input signal of the snow–ice system, and this dataset will be useful to improve the interpretation of paleoclimate records and promote a better understanding of the post-depositional processes affecting the isotopic signal in ice cores. This dataset represents a benchmark for the evaluation of isotope-enabled general circulation models. Here, the ECHAM6-wiso output was compared to experimental data, showing moderately good relationships for δ18O and δ2H but not for d-excess, nonetheless marking a substantial improvement from the previous release of the model.